A phenomenological investigation of an English storyteller - Laely Nuriyah; Maman Fathurrohman; Achmad Hufad (International Journal of Language Teaching and Education, 2021)
This research aimed to figure out what a storyteller's phenomenology was like. The method was phenomenological, and data was collected through interviews, questionnaires, documents, and data triangulation. According to the findings of this study, a storyteller can improve English language skills in four different areas. According to the findings of this study, students can improve their English language skills by telling stories. Several recommendations were made based on the previous conclusions. First, the researcher suggests that all of this research be continued by other researchers, particularly in digital storytelling with stories containing local content to help students understand and learn about Indonesian culture while also improving their ability to speak English. Second, the researcher hopes that the findings of this study will inspire students to learn more about storytelling.